JNK signaling controls border cell cluster integrity and collective cell migration. - Llense, F.; Martín-Blanco, E. (Current Biology, 2008)
Collective cell movement is a mechanism for invasion identified in many developmental events. Examples include the movement of lateral-line neurons in Zebrafish, cells in the inner blastocyst, and metastasis of epithelial tumors [1]. One key model to study collective migration is the movement of border cell clusters in Drosophila. Drosophila egg chambers contain 15 nurse cells and a single oocyte surrounded by somatic follicle cells. At their anterior end, polar cells recruit several neighboring follicle cells to form the border cell cluster [2]. By stage 9, and over 6 hr, border cells migrate as a cohort between nurse cells toward the oocyte. The specification and directionality of border cell movement are regulated by hormonal and signaling mechanisms [3]. However, how border cells are held together while they migrate is not known. Here, we show that a negative-feedback loop controlling JNK activity regulates border cell cluster integrity. JNK signaling modulates contacts between border cells and between border cells and substratum to sustain collective migration by regulating several effectors including the polarity factor Bazooka and the cytoskeletal adaptor D-Paxillin. We anticipate a role for the JNK pathway in controlling collective cell movements in other morphogenetic and clinical models.